Analisis Profil Latar Belakang Ekonomi dan Ketersediaan Fasilitas Teknologi terhadap Motivasi Belajar Kimia - Syukri Ramadhani; Eka Yusmaita; Jon Efendi (Universitas Negeri Padang, 2026)
This study aims to analyze the socioeconomic background and access to technological resources of 10th-grade students at SMA Negeri 5 Padang, as well as their impact on motivation to learn chemistry. Using a descriptive survey approach with a cross-sectional design, data were collected from 36 students via a questionnaire and analyzed using descriptive statistics and Rasch modeling. The results indicate that the majority of students come from lower-middle-income families. There is a paradox: while 100% of students own smartphones, only 25% use them for learning. Although students’ intrinsic motivation was low, their extrinsic motivation regarding the need for digital media was very high, and Rasch analysis revealed that the highest motivation was actually found among students from low-income families with independent access to smartphones. Therefore, this study recommends the development of interactive, mobile-friendly, and data-efficient smartphone-based chemistry learning media to bridge the economic gap and enhance students’ learning motivation in an inclusive manner.